Foreign Direct Investment and Domestic Child Labor. Issue 2 (24th May 2016) - Chaudhuri, Sarbajit; Dwibedi, Jayanta Kumar
Abstract: Empirical evidence suggests that use of child labor as domestic help has increased significantly in recent years although the overall incidence of child labor across the globe has declined satisfactorily. This should draw the attention of economists and policymakers because domestic child labor is considered as exploitative and in many cases hazardous. This paper purports to explain this apparently perplexing finding theoretically in terms of a three‐sector general equilibrium model with a nontraded sector where only child labor is used to render services to the richer section of the society. The analysis shows how FDI‐led economic growth increases the size of the services sector although it lowers the overall incidence of child labor in the economy and improves the welfare of the poor families that supply child labor. Finally, a composite policy has been recommended that can deal with all three aspects favorably.